Treatment Options for Troublesome Itch - Sumika Toyama; Mitsutoshi Tominaga; Kenji Takamori (MDPI AG, 2022)
Itch (or pruritus) is an unpleasant sensation, inducing the desire to scratch. It is also a major and distressing symptom of many skin and systemic diseases. The involvement of histamine, which is a major itch mediator, has been extensively examined. Recent studies suggest that histamine-independent pathways may play roles in chronic itch. Therefore, antihistamines are not always effective in the treatment of patients with chronic itch. The development of biologics and κ-opioid receptor (KOR) agonists has contributed to advances in the treatment of itch; however, since biologics are expensive for patients to purchase, some patients may limit or discontinue their use of these agents. Furthermore, KOR agonists need to be prescribed with caution due to risks of side effects in the central nervous system. Janus kinase (JAK) inhibitors are sometimes associated with side effects, such as infection. In this review, we summarize antidepressants, antineuralgics, cyclosporine A, antibiotics, crotamiton, phosphodiesterase 4 inhibitor, botulinum toxin type A, herbal medicines, phototherapy, and acupuncture therapy as itch treatment options other than antihistamines, biologics, opioids, and JAK inhibitors; we also explain their underlying mechanisms of action.